The Implementation of Guessing Game to Improve The Speaking Ability of EFL Students in Excellent Course, Kampung Inggris, Pare, Kediri - Pratiwi Tristin Puspitasari (EDUCAFL : Journal of Education of English as Foreign Language, 2021)
Speaking English has been one of the most challenging skill for EFL students to master. Additionally, students should learn vocabulary, grammar, and pronunciation in order to master speaking skill. The fluency and appropriateness of students’ speaking abilities should be improved. Speaking problems are common among students, including a lack of vocabulary, poor grammar and spelling, the last is the use of mother tongue. The researcher distributes a questionnaire to the participants in order to identify the students’ speaking difficulties and overcome them through a joyful Guessing Game technique. The participant in this study were students from Excellent Course, Kampung Inggris, Pare, Kediri, who were in speaking class with various school levels. In conducting this research Classroom Action Research as a method and Guessing Game as a teaching strategy. The study was conducted in a specific class for a week. The total number of the students participating in this study was 45 students, and they are divided into 3 classes in “Improving Speaking Class”. The instruments of this research are pre-test, post-test, speaking rubrics from Hugher (2003:131), and a questionnaire adapted from Ratna S, et al. (2017:33) and Djasminar A, et al (2012). The data was calculated using Ms. Excel. The result of the study shows that only 27% students succeed in doing the pre-test before implementing guessing game. Surprisingly, after guessing game was implemented the number has increased into 62% of the students proven to be a success in the post-test. It is reasonable to conclude that using guessing game to teach speaking is success. Furthermore, the students responded positively to being taught via guessing game and they seemed to enjoy the learning process. The outcome of the students’ perception questionnaire demonstrates this.